Impact of Surfactant Chemistry on Bubble Column Systems. Issue 4 (28th February 2014) - McClure, Dale D.; Deligny, Julien; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Abstract The impact of surfactant addition on the overall holdup, drag coefficient, and bubble size distribution (BSD) in a bubble column operating at industrially relevant superficial velocities was analyzed. A range of surfactants was examined, including alcohols, sugars, and antifoaming agents. It was ascertained that the effect of a surfactant on the holdup and BSD could be related to the chemical structure of the compound, specifically its hydrophilic/hydrophobic nature as characterized by the octanol/water partition coefficient. Addition of 2‐propanol to an air/water system induces a behavior similar to the fermentation media used in aerobic bioprocesses, meaning that such a system can be applied as a meaningful physical analogue in pilot‐scale experimentation.